PERAN MEDIATOR DALAM PENYELESAIAN PERKARA PERDATA DI PENGADILAN NEGERI - Effendi, Devi Rianti (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
The court without trying to resolve it first at the nagari level through the Adat NagariKerapatan Institute (KAN). In addition to the problem of lack of trust in customary institutions, filing a case directly with the Court is considered to have a value of prestige and self-esteem in this case which makes it difficult for the Judge to attempt to reconcile parties who litigate in addition to the absence of strict regulations regarding peace efforts in the Court. Based on the description of the background above, the writer wants to conduct research and realize in a scientific work in the form of a thesis entitled